Study on rheological properties of polymer/pitch compositions - Brzozowska, T.; Zieliński, J. (Polimery, 2022)
The effect of addition of 10 wt. % of a polymer on rheological characteristics of coal tar pitch determined in temperature range 90-150 oC and shear rate up to 1000 s-1 has been studied (Table 1 and 2, Fig. 1-5). The following polymers were used: poly(vinyl chloride) - PVC, atactic polypropylene - PP-a, butadiene/styrene copolymer - SBR, poly(ethylene terephthalate) - PET, cumarone-indene resin - CIR, unsaturated polyester resin - UP or poly(oxyethylene)diol - PEG. It was found that these compositions could be treated as shear diluted non-Newtonian fluids i.e. thixotropic systems (Fig. 5). Strong structural interaction pitch - polymer was found the strongest in case of PET. The system pitch - PVC was studied using cone + plate measurement system, limiting the polymer degradation (because of the possibility of PVC degradation at temp. > 120 oC). For the other compositions a cylindrical measurement system was applied.